Simulación del desgaste del material AISI 1020 bajo condiciones de corrosión-erosión (2020)
Wind turbines are important devices in the generation of clean energy in places where there are usable air currents. However, they are easily affected by the corrosion-erosion phenomenon given the environmental conditions, such as: the presence of particles and aggressive agents in the environment, as well as the humidity typical of the tropics. In this work, two previously developed models of erosion and Corrosion were analyzed and adapted to the representative environmental conditions of at least two places localized in Colombia. La Guajira was taken like the most important given its aggressiveness. Based on the above, the following conditions were taken: the impact speed of 15m / s, particle size of 375μm, percentage of (NaCl) in the environment of 3.5%, among others. The results obtained allowed obtaining wear rates, as well as the quantification of the incidence of erosive phenomenon. Those observations confirmed that geometries where particles impact in angles around 30º will be highly affected by erosion.